Microparticle of Phenolic Compound and its Herbal Extracts: Fabrication, Characterization, and Therapeutic Application - Aisia Nurul Jasmine; Finna Setiawan; Kartini; Veerakiet Boonkanokwong; Aditya Trias Pradana (Jurnal Penelitian Pendidikan IPA, 2026)
Phenolic compounds in herbal extracts exhibit broad therapeutic potential (antioxidant, anti-inflammatory, antidiabetic, antimicrobial, neuroprotective), yet are hindered by instability, poor solubility, and low bioavailability—critical limitations restricting their use in pharmaceutical and functional food products. This review aims to evaluate the fabrication techniques, characterization methods, and therapeutic applications of phenolic microparticles to address these research gapsA systematic approach was employed through searches on Google Scholar and ScienceDirect, applying inclusion criteria for original full-text studies reporting fabrication techniques, polymers, characterizations, or biological activities. Dominant techniques included spray drying, freeze drying, emulsification/coacervation, and ionic gelation, with primary wall materials comprising maltodextrin, chitosan, pectin, and PLGA. Characterization encompassed FTIR, SEM, DSC/TGA, particle size analysis, encapsulation efficiency (>70%), and release profiles in SGF/SIF media. Results demonstrate that microencapsulation enhances storage stability, gastrointestinal resilience, and bioavailability of phenolic compounds from diverse sources (bauhinia, moringa, citrus), while preserving antioxidant and antidiabetic activities. This review contributes to standardized formulation development for herbal pharmaceuticals and functional foods, although randomized clinical trials remain necessary to validate clinical benefits.